Estimating and Evaluating Roughness Length and Displacement Height in Heterogeneous Urban Environments - Jason P. Horne; Ying Pan; Kenneth J. Davis (Boundary-Layer Meteorology, 2026)
The roughness length ( $$z_0$$ z 0 ) and displacement height ( $$z_d$$ z d ) are essential surface-layer parameters in numerical models (e.g., weather, climate, wall-modeled LES, etc.). This work evaluates the consistency of $$z_0$$ z 0 and $$z_d$$ z d estimates from morphometric and anemometric methods using data from two eddy-covariance flux towers (AmeriFlux US-INg and US-INc) in Indianapolis, IN. Results show inconsistencies in estimated $$z_0$$ z 0 and $$z_d$$ z d values depending on the chosen method. The two evaluated anemometric methods estimate non-physical values of $$z_d$$ z d when compared to roughness elements surrounding both towers. Additionally, predictions of mean wind speed using surface-layer similarity theory with morphometric estimates exhibit a bias during near-neutral and stable conditions relative to observations. The overestimation of mean wind speed by surface layer similarity theory is consistent with previous observational and modeling studies in urban areas, suggesting that the application of similarity theories to urban environments may have limitations. Differentiation of vegetation from built structures appears to impact morphometric $$z_0$$ z 0 and $$z_d$$ z d estimates, particularly where vegetation is abundant; however, it has little impact on correcting biases in the similarity theory. Specifically, we find that existing similarity theories using morphometric estimates underestimate integral velocity and length scales, and the degree of underestimation depends on the stability conditions. Accounting for the degree of anisotropy in surface-layer turbulence helps reduce the biases between similarity theories and observations during unstable conditions, but not in near-neutral cases. Future work is needed to identify the cause of such biases for near-neutral conditions.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Evaluating surface fluxes in WRF using eddy-covariance flux measurements in the Western and Eastern U.S. - Fan Wu; Kenneth J. Davis; Li Zhang; Ray G. Anderson; Jason P. Horne; Sarah Goslee; William Munger; Chenxia Cai; Yu Yan Cui; Zhan Zhao; Min Zhong (Agricultural and Forest Meteorology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Outcomes from a STEM Education Program for Elementary School Students in Medically Underserved Areas and Populations - Muriel R. Statman; Ethan N. Eisenstein; Madeleine Brown; Marcelo M. Sleiman; Rebecca B. Riggins; Jackie Eyl; Dorothy Jones-Davis; Liza Manfred; Dia Stone; Catherine J. Scharon; Laurel Harrington; Chiranjeev Dash; et al. (Journal of Cancer Education, 2026)

Nicotinamide riboside supplementation restores microglial health and improves cognition in aged male mice - Ramkumar Thiyagarajan; Rupadevi Muthaiah; Bhavana Sreevelu; Owen P. Treanor; Yonas Redae; Reem Berman; Anna L. Davis; Nanda Yellapu; Spencer R. Rosario; Lee D. Chaves; Kenneth L. Seldeen; Bruce R. Troen (GeroScience, 2025)
Cognitive impairment affects 1 in 6 individuals over 60, with over 75 million projected by 2030. Age-related changes in microglial function and declining nicotinamide adenine dinucleotide (NAD + ) levels may contribute to cognitive decline. Although nicotinamide riboside (NR) supplementation can restore NAD + levels in aged mice, its effects on microglial phenotype and cognition during normal aging remain unclear. We assessed cognitive function, neuroinflammation, and microglial gene expression in 6-month (Young) and 22-month (Aged) mice, along with aged mice supplemented with NR (Aged + NR; 400 mg/kg body weight) for 8 weeks. Aged mice exhibited impaired cognition and increased gene expression related to neuroinflammation. NR supplementation improved or prevented the decline in nest-building ability, Y-maze spontaneous alternation, and novel object recognition, which are reflective of instrumental activities of daily living, spatial working memory, and recognition memory. NR supplementation diminished microglial (IBA1) and astrocytic (GFAP) activation, resembling the young phenotype. Gene expression profiling revealed reduced microglial activation, inflammatory pathways, and chemokine production in Aged + NR mice, along with upregulation of genes associated with learning, memory, and gliogenesis. NR lowered transcriptional signatures from age-dependent (ADEM) and disease-associated (DAM) microglia and enhanced homeostatic state profiles. Metabolic pathway analysis of microglial transcripts indicated that NR suppressed age-induced increases in fatty acid metabolism. This was supported by immunostaining, which showed reduced lipoprotein lipase (LPL), a DAM marker, in the cortex and hippocampus. Overall, NR appeared to mitigate age-related cognitive decline by shifting microglial gene expression and metabolism toward a younger phenotype, suggesting potential therapeutic relevance for healthy brain aging.

Association of Immunogenicity and Drug Exposure and the Importance of Target Engagement in ADA Development: A Clinical Case Study of Anti-SARS-CoV-2 Biotherapeutics - Susan C. Irvin; Samit Ganguly; Zhiqiang Wang; Zhongqing Will He; Marguerite Alejandro; Kaitlin Donohue; Chinnasamy Elango; Chris Gallo; Stephen Guttmann; Shawn Kalicharan; Kristina Kameron; James Laird; et al. (The AAPS Journal, 2025)
The administration of therapeutic proteins, such as monoclonal antibodies (mAbs) may result in the formation of anti-drug antibodies (ADA), but there is limited publicly available data for biotherapeutics with exogenous targets or with targets in low abundance systemically. ADAs can impact a biotherapeutic’s safety, efficacy, and pharmacokinetics, so evaluation of immunogenicity is required for all therapeutic proteins. This analysis sought to evaluate the immunogenicity of two mAbs against COVID-19, casirivimab (CAS) and imdevimab (IMD) administered as a cocktail (CAS + IMD), in multiple clinical trials across different participant populations to add knowledge about the immunogenicity risk of protein therapeutics against exogenous targets and the association between immunogenicity and drug exposure. Overall, the incidence of treatment-boosted and treatment-emergent ADAs and neutralizing antibodies in both disease treatment and prophylaxis settings were low (i.e., < 11%). Participants in these studies were followed for up to 225 days post-last dose. Over time, the incidence of treatment-emergent and treatment-boosted immunogenicity for each mAb increased, but the rates and titers remained low overall; when it developed, patients usually developed ADA to both mAbs. Frequency of administration, dose, and route of administration did not appear to impact rates of immunogenicity. Concentrations of CAS and IMD were similar between participants of different immunogenicity status, indicating immunogenicity of CAS and IMD had no impact on pharmacokinetics of these mAbs; there was also no observed impact on safety or efficacy. The data presented here may provide supportive information for assessing the immunogenicity risk of protein therapeutics with exogenous targets. Graphical Abstract

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Identifying silver ore sources for the earliest coins of Athens - Gillan Davis; Janne Blichert-Toft; Liesel Gentelli; Damian B. Gore; Kenneth A. Sheedy; Francis Albarède (Archaeological and Anthropological Sciences, 2025)
This study addresses longstanding questions concerning the ore sources used in the first series of coins of ancient Athens known as the Wappenmϋnzen (c.540-c.500 BCE) by combining comprehensive numismatic data on 22 coins (16 new and 6 legacy analyses) with lead isotope and surface elemental measurements (MC-ICP-MS and XRF). It finds usage of ores from Spain to Romania and Türkiye and frequent mixing. This upends current thinking based on a (mis)interpretation of historical sources which argues that the tyrant Peisistratos and his sons, who ruled Athens during the period, sourced most silver from the districts of Mt Pangaion and Strymon River in northern Greece and that silver did not flow from the western Mediterranean into their coinage. The data suggest that domestic ‘Lavrion’ mines of Athens did not contribute to the ore stock of the Wappenmϋnzen until the subsequent production of the ‘owl’ series when it was also used in some Wappenmϋnzen fractions and show that there is no correlation between coin types and ore sources. Elemental compositions nuance our understanding of the coins, but do not shed light on provenance. Together, these new findings force a reappraisal of numismatic and historical perceptions of the period of the Athenian tyranny in the lead up to democracy, not least because the multiple silver sources point to trading relationships with a greater variety of regions than previously contemplated.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Leveraging Maker Learning in STEM to Promote Children’s Interest in Cancer Research: A Pilot Program - Kenneth P. Tercyak; Mary Rose Yockel; Jacqueline Eyl; Chiranjeev Dash; Dorothy Jones-Davis; Marcelo M. Sleiman; Liza Manfred; Dia Stone; Karen Howenstein; Denise Flessate Harley; Mingqian Liu; Catherine J. Scharon; et al. (Journal of Cancer Education, 2024)

Population Pharmacokinetics of Casirivimab and Imdevimab in Pediatric and Adult Non-Infected Individuals, Pediatric and Adult Ambulatory or Hospitalized Patients or Household Contacts of Patients Infected with SARS-COV-2 - Kuan-Ju Lin; Kenneth C. Turner; Maria Rosario; Lutz O. Harnisch; John D. Davis; A. Thomas DiCioccio (Pharmaceutical Research, 2024)
Introduction Casirivimab (CAS) and imdevimab (IMD) are two fully human monoclonal antibodies that bind different epitopes on the receptor binding domain of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and block host receptor interactions. CAS + IMD and was developed for the treatment and prevention of SARS-CoV-2 infections. Methods A population pharmacokinetic (PopPK) analysis was conducted using pooled data from 7598 individuals from seven clinical studies to simultaneously fit concentration–time data of CAS and IMD and investigate selected covariates as sources of variability in PK parameters. The dataset comprised CAS + IMD-treated pediatric and adult non-infected individuals, ambulatory or hospitalized patients infected with SARS-CoV-2, or household contacts of patients infected with SARS-CoV-2. Results CAS and IMD concentration–time data were both appropriately described simultaneously by a two-compartment model with first-order absorption following subcutaneous dose administration and first-order elimination. Clearance estimates of CAS and IMD were 0.193 and 0.236 L/day, respectively. Central volume of distribution estimates were 3.92 and 3.82 L, respectively. Among the covariates identified as significant, body weight and serum albumin had the largest impact (20–34%, and ~ 7–31% change in exposures at extremes, respectively), while all other covariates resulted in small differences in exposures. Application of the PopPK model included simulations to support dose recommendations in pediatrics based on comparable exposures of CAS and IMD between different weight groups in pediatrics and adults following weight-based dosing regimens. Conclusions This analysis provided important insights to characterize CAS and IMD PK simultaneously in a diverse patient population and informed pediatric dose selection.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Correction to: Artisanal and small-scale gold mining and biodiversity: a global literature review - Imelda M. Dossou Etui; Malgorzata Stylo; Kenneth Davis; David C. Evers; Vera I. Slaveykova; Caroline Wood; Mark E. H. Burton (Ecotoxicology, 2024)

Artisanal and small-scale gold mining and biodiversity: a global literature review - Imelda M. Dossou Etui; Malgorzata Stylo; Kenneth Davis; David C. Evers; Vera I. Slaveykova; Caroline Wood; Mark E. H. Burton (Ecotoxicology, 2024)

Recombinant Human Perlecan DV and Its LG3 Subdomain Are Neuroprotective and Acutely Functionally Restorative in Severe Experimental Ischemic Stroke - Ifechukwude Joachim Biose; Ibolya Rutkai; Bryan Clossen; Gary Gage; Kenneth Schechtman; H. Davis Adkisson; Gregory J. Bix (Translational Stroke Research, 2023)
Despite recent therapeutic advancements, ischemic stroke remains a major cause of death and disability. It has been previously demonstrated that ~ 85-kDa recombinant human perlecan domain V (rhPDV) binds to upregulated integrin receptors (α2β1 and α5β1) associated with neuroprotective and functional improvements in various animal models of acute ischemic stroke. Recombinant human perlecan laminin-like globular domain 3 (rhPDV LG3 ), a 21-kDa C-terminal subdomain of rhPDV, has been demonstrated to more avidly bind to the α2β1 integrin receptor than its parent molecule and consequently was postulated to evoke significant neuroprotective and functional effects. To test this hypothesis, fifty male C57Bl/6 J mice studied in a t-MCAO model were randomly allocated to either rhPDV treatment, rhPDV LG3 , or equivalent volume of PBS at the time of reperfusion in a study where all procedures and analyses were conducted blind to treatment. On post-MCAO day 7, 2,3,5-triphenyltetrazolium chloride staining of brain slices was used to quantify infarct volume. We observed that treatment with rhPDV LG3 reduced infarct volume by 65.6% ( p = 0.0001), improved weight loss ( p < 0.05), and improved functional outcome measures ( p < 0.05) when compared to PBS controls, improvements which were generally greater in magnitude than those observed for 2 mg/kg of rhPDV. In addition, treatment with 6 mg/kg of rhPDV LG3 was observed to significantly reduce mortality due to stroke in one model, an outcome not previously observed for rhPDV. Our initial findings suggest that treatment with rhPDV LG3 provides significant improvement in neuroprotective and functional outcomes in experimental stroke models and that further investigation of rhPDV LG3 as a novel neuroprotective therapy for patients with stroke is warranted.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Mercury and artisanal and small-scale gold mining: Review of global use estimates and considerations for promoting mercury-free alternatives - Susan Keane; Ludovic Bernaudat; Kenneth J. Davis; Malgorzata Stylo; Nellia Mutemeri; Patience Singo; Pontsho Twala; Itai Mutemeri; Anne Nakafeero; Imelda Dossou Etui (Ambio, 2023)
Artisanal and small-scale gold mining (ASGM) is present in over 80 countries, employing about 15 million miners and serving as source of livelihood for millions more. The sector is estimated to be the largest emitter of mercury globally. The Minamata Convention on Mercury seeks to reduce and, where feasible, eliminate mercury use in the ASGM. However, the total quantity of mercury used in ASGM globally is still highly uncertain, and the adoption of mercury-free technologies has been limited. This paper presents an overview of new data, derived from Minamata ASGM National Action Plan submissions, that can contribute to refining estimates of mercury use in ASGM, and then assesses technologies that can support the phase out mercury use in ASGM while increasing gold recovery. The paper concludes with a discussion of social and economic barriers to adoption of these technologies, illustrated by a case study from Uganda.

Barriers to completion of cascade genetic testing: how can we improve the uptake of testing for hereditary breast and ovarian cancer syndrome? - Ryan Matthew Kahn; Muhammad Danyal Ahsan; Eloise Chapman-Davis; Kevin Holcomb; Roni Nitecki; Jose Alejandro Rauh-Hain; Rana Khan Fowlkes; Francesca Tubito; Maira Pires; Paul J Christos; Kaitlyn Tkachuk; Hannah Krinsky; et al. (Familial Cancer, 2023)

Interannual, sub-seasonal and spatial variations in growing season surface heat fluxes for the U.S. Corn Belt - Mikael P. Hiestand; Andrew M. Carleton; Kenneth J. Davis (Agricultural and Forest Meteorology, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Precipitation alters the CO 2 effect on water‐use efficiency of temperate forests - Soumaya Belmecheri; R. Stockton Maxwell; Alan H. Taylor; Kenneth J. Davis; Rossella Guerrieri; David J. P. Moore; Shelly A. Rayback (Global Change Biology, 2021)
Increasing water‐use efficiency (WUE), the ratio of carbon gain to water loss, is a key mechanism that enhances carbon uptake by terrestrial vegetation under rising atmospheric CO 2 ( c a ). Existing theory and empirical evidence suggest a proportional WUE increase in response to rising c a as plants maintain a relatively constant ratio between the leaf intercellular ( c i ) and ambient ( c a ) partial CO 2 pressure ( c i / c a ). This has been hypothesized as the main driver of the strengthening of the terrestrial carbon sink over the recent decades. However, proportionality may not characterize CO 2 effects on WUE on longer time‐scales and the role of climate in modulating these effects is uncertain. Here, we evaluate long‐term WUE responses to c a and climate from 1901 to 2012 CE by reconstructing intrinsic WUE (iWUE, the ratio of photosynthesis to stomatal conductance) using carbon isotopes in tree rings across temperate forests in the northeastern USA. We show that iWUE increased steadily from 1901 to 1975 CE but remained constant thereafter despite continuously rising c a . This finding is consistent with a passive physiological response to c a and coincides with a shift to significantly wetter conditions across the region. Tree physiology was driven by summer moisture at multi‐decadal time‐scales and did not maintain a constant c i / c a in response to rising c a indicating that a point was reached where rising CO 2 had a diminishing effect on tree iWUE. Our results challenge the mechanism, magnitude, and persistence of CO 2 's effect on iWUE with significant implications for projections of terrestrial productivity under a changing climate.

Linking science and policy to support the implementation of the Minamata Convention on Mercury - Henrik Selin; Susan Egan Keane; Shuxiao Wang; Noelle E. Selin; Kenneth Davis; Dominique Bally (Ambio, 2018)

Longer exercise duration delays post-exercise recovery of cardiac parasympathetic but not sympathetic indices - Scott Michael; Ollie Jay; Kenneth S. Graham; Glen M. Davis (European Journal of Applied Physiology, 2017)

Submaximal exercise intensity modulates acute post-exercise heart rate variability - Scott Michael; Ollie Jay; Mark Halaki; Kenneth Graham; Glen M. Davis (European Journal of Applied Physiology, 2016)

AMG2850, a potent and selective TRPM8 antagonist, is not effective in rat models of inflammatory mechanical hypersensitivity and neuropathic tactile allodynia - Sonya G. Lehto; Andy D. Weyer; Maosheng Zhang; Beth D. Youngblood; Judy Wang; Weiya Wang; Patrick C. Kerstein; Carl Davis; Kenneth D. Wild; Cheryl L. Stucky; Narender R. Gavva (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

A New Species of Docodon (Mammaliaformes: Docodonta) from the Upper Jurassic Morrison Formation and a Reassessment of Selected Craniodental Characters in Basal Mammaliaforms - Guillermo W. Rougier; Amir S. Sheth; Kenneth Carpenter; Lucas Appella-Guiscafre; Brian M. Davis (Journal of Mammalian Evolution, 2015)

Development and Validation of a UPLC Method for Rapid and Simultaneous Analysis of Proton Pump Inhibitors - Richard T. Addo; Kenneth Davis; Ruhi Ubale; Joel S. Owen; E. Blake Watkins (AAPS PharmSciTech, 2015)

A Novel Approach to Evaluate the Pharmacokinetic Biocomparability of a Monoclonal Antibody Derived from Two Different Cell Lines Using Simultaneous Crossover Design - Chao Han; Thomas S. McIntosh; Brian J. Geist; Trina Jiao; Thomas A. Puchalski; Kenneth M. Goldberg; Tong-Yuan Yang; Charles E. Pendley; Honghui Zhou; Hugh M. Davis (The AAPS Journal, 2014)

Land-Surface Heterogeneity Effects in the Planetary Boundary Layer - Brian P. Reen; David R. Stauffer; Kenneth J. Davis (Boundary-Layer Meteorology, 2014)

Evaluating atmospheric CO 2 inversions at multiple scales over a highly inventoried agricultural landscape - Andrew E. Schuh; Thomas Lauvaux; Tristram O. West; A. Scott Denning; Kenneth J. Davis; Natasha Miles; Scott Richardson; Marek Uliasz; Erandathie Lokupitiya; Daniel Cooley; Arlyn Andrews; Stephen Ogle (Global Change Biology, 2013)
An intensive regional research campaign was conducted by the N orth A merican Carbon Program ( NACP ) in 2007 to study the carbon cycle of the highly productive agricultural regions of the M idwestern U nited S tates. Forty‐five different associated projects were conducted across five US agencies over the course of nearly a decade involving hundreds of researchers. One of the primary objectives of the intensive campaign was to investigate the ability of atmospheric inversion techniques to use highly calibrated CO 2 mixing ratio data to estimate CO 2 flux over the major croplands of the U nited S tates by comparing the results to an inventory of CO 2 fluxes. Statistics from densely monitored crop production, consisting primarily of corn and soybeans, provided the backbone of a well studied bottom‐up inventory flux estimate that was used to evaluate the atmospheric inversion results. Estimates were compared to the inventory from three different inversion systems, representing spatial scales varying from high resolution mesoscale ( PSU ), to continental ( CSU ) and global (CarbonTracker), coupled to different transport models and optimization techniques. The inversion‐based mean CO 2 ‐C sink estimates were generally slightly larger, 8–20% for PSU , 10–20% for CSU , and 21% for CarbonTracker, but statistically indistinguishable, from the inventory estimate of 135 TgC. While the comparisons show that the MCI region‐wide C sink is robust across inversion system and spatial scale, only the continental and mesoscale inversions were able to reproduce the spatial patterns within the region. In general, the results demonstrate that inversions can recover CO 2 fluxes at sub‐regional scales with a relatively high density of CO 2 observations and adequate information on atmospheric transport in the region.

Relationship between anthropometric factors, radiation exposure, and colon cancer incidence in the Life Span Study cohort of atomic bomb survivors - Erin O. Semmens; Kenneth J. Kopecky; Eric Grant; Robert W. Mathes; Nobuo Nishi; Hiromi Sugiyama; Hiroko Moriwaki; Ritsu Sakata; Midori Soda; Fumiyoshi Kasagi; Michiko Yamada; Saeko Fujiwara; et al. (Cancer Causes & Control, 2013)

Terrestrial biosphere models need better representation of vegetation phenology: results from the N orth A merican C arbon P rogram S ite S ynthesis - Andrew D. Richardson; Ryan S. Anderson; M. Altaf Arain; Alan G. Barr; Gil Bohrer; Guangsheng Chen; Jing M. Chen; Philippe Ciais; Kenneth J. Davis; Ankur R. Desai; Michael C. Dietze; Danilo Dragoni; et al. (Global Change Biology, 2012)
Phenology, by controlling the seasonal activity of vegetation on the land surface, plays a fundamental role in regulating photosynthesis and other ecosystem processes, as well as competitive interactions and feedbacks to the climate system. We conducted an analysis to evaluate the representation of phenology, and the associated seasonality of ecosystem‐scale CO 2 exchange, in 14 models participating in the N orth A merican C arbon P rogram S ite S ynthesis. Model predictions were evaluated using long‐term measurements (emphasizing the period 2000–2006) from 10 forested sites within the A meri F lux and F luxnet‐ C anada networks. In deciduous forests, almost all models consistently predicted that the growing season started earlier, and ended later, than was actually observed; biases of 2 weeks or more were typical. For these sites, most models were also unable to explain more than a small fraction of the observed interannual variability in phenological transition dates. Finally, for deciduous forests, misrepresentation of the seasonal cycle resulted in over‐prediction of gross ecosystem photosynthesis by +160 ± 145 g C m −2 yr −1 during the spring transition period and +75 ± 130 g C m −2 yr −1 during the autumn transition period (13% and 8% annual productivity, respectively) compensating for the tendency of most models to under‐predict the magnitude of peak summertime photosynthetic rates. Models did a better job of predicting the seasonality of CO 2 exchange for evergreen forests. These results highlight the need for improved understanding of the environmental controls on vegetation phenology and incorporation of this knowledge into better phenological models. Existing models are unlikely to predict future responses of phenology to climate change accurately and therefore will misrepresent the seasonality and interannual variability of key biosphere–atmosphere feedbacks and interactions in coupled global climate models.

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Resistance to the Translation Initiation Inhibitor Silvestrol is Mediated by ABCB1/P-Glycoprotein Overexpression in Acute Lymphoblastic Leukemia Cells - Sneha V. Gupta; Ellen J. Sass; Melanie E. Davis; Ryan B. Edwards; Gerard Lozanski; Nyla A. Heerema; Amy Lehman; Xiaoli Zhang; David Jarjoura; John C. Byrd; Li Pan; Kenneth K. Chan; et al. (The AAPS Journal, 2011)

C4 protein of Beet severe curly top virus is a pathomorphogenetic factor in Arabidopsis - Jungan Park; Hyun-Sik Hwang; Kenneth J. Buckley; Jong-Bum Park; Chung-Kyun Auh; Dong-Giun Kim; Sukchan Lee; Keith R. Davis (Plant Cell Reports, 2010)

Airborne Lidar Observations of the Transition Zone Between the Convective Boundary Layer and Free Atmosphere During the International H2O Project (IHOP) in 2002 - Jeffrey S. Grabon; Kenneth J. Davis; Christoph Kiemle; Gerhard Ehret (Boundary-Layer Meteorology, 2010)

Role of Convective Flow in Carmustine Delivery to a Brain Tumor - Davis Yohanes Arifin; Kam Yiu Timothy Lee; Chi-Hwa Wang; Kenneth A. Smith (Pharmaceutical Research, 2009)

A Case Study of CO2, CO and Particles Content Evolution in the Suburban Atmospheric Boundary Layer Using a 2-μm Doppler DIAL, a 1-μm Backscatter Lidar and an Array of In-situ Sensors - Fabien Gibert; Irène Xuéref-Rémy; Lilian Joly; Martina Schmidt; Juan Cuesta; Kenneth J. Davis; Michel Ramonet; Pierre H. Flamant; Bertrand Parvitte; Virginie Zéninari (Boundary-Layer Meteorology, 2008)

Dissociation of force decline from calcium decline by preload in isolated rabbit myocardium - Michelle M. Monasky; Kenneth D. Varian; Jonathan P. Davis; Paul M. L. Janssen (Pflügers Archiv - European Journal of Physiology, 2008)

Using Light-Use and Production Efficiency Models to Predict Photosynthesis and Net Carbon Exchange During Forest Canopy Disturbance - Bruce D. Cook; Paul V. Bolstad; Jonathan G. Martin; Faith Ann Heinsch; Kenneth J. Davis; Weiguo Wang; Ankur R. Desai; Ron M. Teclaw (Ecosystems, 2008)

A note on the top-down and bottom-up gradient functions over a forested site - Weiguo Wang; Kenneth J. Davis; Chuixiang Yi; Edward G. Patton; Martha P. Butler; Daniel M. Ricciuto; Peter S. Bakwin (Boundary-Layer Meteorology, 2007)

Physical activity and mental well-being in older people participating in the Better Ageing Project - Kenneth R. Fox; Afroditi Stathi; Jim McKenna; Mark G. Davis (European Journal of Applied Physiology, 2007)

Physical activity patterns assessed by accelerometry in older people - Mark G. Davis; Kenneth R. Fox (European Journal of Applied Physiology, 2007)

A Case Study on the Effects of Heterogeneous Soil Moisture on Mesoscale Boundary-Layer Structure in the Southern Great Plains, U.S.A. Part II: Mesoscale Modelling - Brian P. Reen; David R. Stauffer; Kenneth J. Davis; Ankur R. Desai (Boundary-Layer Meteorology, 2006)

A Case Study on the Effects of Heterogeneous Soil Moisture on Mesoscale Boundary-Layer Structure in the Southern Great Plains, U.S.A. Part I: Simple Prognostic Model - Ankur R. Desai; Kenneth J. Davis; Christoph J. Senff; Syed Ismail; Edward V. Browell; David R. Stauffer; Brian P. Reen (Boundary-Layer Meteorology, 2006)

Modeling and Monitoring of Polymorphic Transformations During the Drying Phase of Wet Granulation - Tiffani D. Davis; Garnet E. Peck; Joseph G. Stowell; Kenneth R. Morris; Stephen R. Byrn (Pharmaceutical Research, 2004)

In situ Monitoring of Wet Granulation Using Online X-Ray Powder Diffraction - Tiffani D. Davis; Kenneth R. Morris; Huapeng Huang; Garnet E. Peck; Joseph G. Stowell; Bradley J. Eisenhauer; Jon L. Hilden; David Gibson; Stephen R. Byrn (Pharmaceutical Research, 2003)

The annual cycles of CO 2 and H 2 O exchange over a northern mixed forest as observed from a very tall tower - Kenneth J. Davis; Peter S. Bakwin; Chuixiang Yi; Bradford W. Berger; Conglong Zhao; Ronald M. Teclaw; J. G. Isebrands (Global Change Biology, 2003)
We present the annual patterns of net ecosystem‐atmosphere exchange (NEE) of CO 2 and H2O observed from a 447 m tall tower sited within a mixed forest in northern Wisconsin, USA. The methodology for determining NEE from eddy‐covariance flux measurements at 30, 122 and 396 m above the ground, and from CO 2 mixing ratio measurements at 11, 30, 76, 122, 244 and 396 m is described. The annual cycle of CO 2 mixing ratio in the atmospheric boundary layer (ABL) is also discussed, and the influences of local NEE and large‐scale advection are estimated. During 1997 gross ecosystem productivity (947−18 g C m −2 yr −1 ), approximately balanced total ecosystem respiration (963±19 g C m −2 yr −1 ), and NEE of CO 2 was close to zero (16±19 g C m −2 yr −1 emitted into the atmosphere). The error bars represent the standard error of the cumulative daily NEE values. Systematic errors are also assessed. The identified systematic uncertainties in NEE of CO 2 are less than 60 g C m −2 yr −1 . The seasonal pattern of NEE of CO 2 was highly correlated with leaf‐out and leaf‐fall, and soil thaw and freeze, and was similar to purely deciduous forest sites. The mean daily NEE of CO 2 during the growing season (June through August) was −1.3 g C m −2 day −1 , smaller than has been reported for other deciduous forest sites. NEE of water vapor largely followed the seasonal pattern of NEE of CO 2 , with a lag in the spring when water vapor fluxes increased before CO 2 uptake. In general, the Bowen ratios were high during the dormant seasons and low during the growing season. Evapotranspiration normalized by potential evapotranspiration showed the opposite pattern. The seasonal course of the CO 2 mixing ratio in the ABL at the tower led the seasonal pattern of NEE of CO 2 in time: in spring, CO 2 mixing ratios began to decrease prior to the onset of daily net uptake of CO 2 by the forest, and in fall mixing ratios began to increase before the forest became a net source for CO 2 to the atmosphere. Transport as well as local NEE of CO 2 are shown to be important components of the ABL CO 2 budget at all times of the year.

Regional‐scale measurements of CH 4 exchange from a tall tower over a mixed temperate/boreal lowland and wetland forest - Cindy Werner; Kenneth Davis; Peter Bakwin; Chuixiang Yi; Dale Hurst; Loreen Lock (Global Change Biology, 2003)
The biosphere–atmosphere exchange of methane (CH 4 ) was estimated for a temperate/boreal lowland and wetland forest ecosystem in northern Wisconsin for 1997–1999 using the modified Bowen ratio (MBR) method. Gradients of CH 4 and CO 2 and CO 2 flux were measured on the 447‐m WLEF‐TV tower as part of the Chequamegon Ecosystem–Atmosphere Study (ChEAS). No systematic diurnal variability was observed in regional CH 4 fluxes measured using the MBR method. In all 3 years, regional CH 4 emissions reached maximum values during June–August (24±14.4 mg m −2 day −1 ), coinciding with periods of maximum soil temperatures. In 1997 and 1998, the onset in CH 4 emission was coincident with increases in ground temperatures following the melting of the snow cover. The onset of emission in 1999 lagged 100 days behind the 1997 and 1998 onsets, and was likely related to postdrought recovery of the regional water table to typical levels. The net regional emissions were 3.0, 3.1, and 2.1 g CH 4 m −2 for 1997, 1998, and 1999, respectively. Annual emissions for wetland regions within the source area (28% of the land area) were 13.2, 13.8, and 10.3 g CH 4 m −2 assuming moderate rates of oxidation of CH 4 in upland regions in 1997, 1998, and 1999, respectively. Scaling these measurements to the Chequamegon Ecosystem (CNNF) and comparing with average wetland emissions between 40°N and 50°N suggests that wetlands in the CNNF emit approximately 40% less than average wetlands at this latitude. Differences in mean monthly air temperatures did not affect the magnitude of CH 4 emissions; however, reduced precipitation and water table levels suppressed CH 4 emission during 1999, suggesting that long‐term climatic changes that reduce the water table will likely transform this landscape to a reduced source or possibly a sink for atmospheric CH 4 .

Simulated variations in atmospheric CO 2 over a Wisconsin forest using a coupled ecosystem–atmosphere model - A. Scott Denning; Melville Nicholls; Lara Prihodko; Ian Baker; Pier‐Luigi Vidale; Kenneth Davis; Peter Bakwin (Global Change Biology, 2003)
Ecosystem fluxes of energy, water, and CO 2 result in spatial and temporal variations in atmospheric properties. In principle, these variations can be used to quantify the fluxes through inverse modelling of atmospheric transport, and can improve the understanding of processes and falsifiability of models. We investigated the influence of ecosystem fluxes on atmospheric CO 2 in the vicinity of the WLEF‐TV tower in Wisconsin using an ecophysiological model (Simple Biosphere, SiB2) coupled to an atmospheric model (Regional Atmospheric Modelling System). Model parameters were specified from satellite imagery and soil texture data. In a companion paper, simulated fluxes in the immediate tower vicinity have been compared to eddy covariance fluxes measured at the tower, with meteorology specified from tower sensors. Results were encouraging with respect to the ability of the model to capture observed diurnal cycles of fluxes. Here, the effects of fluxes in the tower footprint were also investigated by coupling SiB2 to a high‐resolution atmospheric simulation, so that the model physiology could affect the meteorological environment. These experiments were successful in reproducing observed fluxes and concentration gradients during the day and at night, but revealed problems during transitions at sunrise and sunset that appear to be related to the canopy radiation parameterization in SiB2.

Simulated and observed fluxes of sensible and latent heat and CO 2 at the WLEF‐TV tower using SiB2.5 - Ian Baker; A. Scott Denning; Niall Hanan; Lara Prihodko; Marek Uliasz; Pier‐Luigi Vidale; Kenneth Davis; Peter Bakwin (Global Change Biology, 2003)
Three years of meteorological data collected at the WLEF‐TV tower were used to drive a revised version of the Simple Biosphere (SiB 2.5) Model. Physiological properties and vegetation phenology were specified from satellite imagery. Simulated fluxes of heat, moisture, and carbon were compared to eddy covariance measurements taken onsite as a means of evaluating model performance on diurnal, synoptic, seasonal, and interannual time scales. The model was very successful in simulating variations of latent heat flux when compared to observations, slightly less so in the simulation of sensible heat flux. The model overestimated peak values of sensible heat flux on both monthly and diurnal scales. There was evidence that the differences between observed and simulated fluxes might be linked to wetlands near the WLEF tower, which were not present in the SiB simulation. The model overestimated the magnitude of the net ecosystem exchange of CO 2 in both summer and winter. Mid‐day maximum assimilation was well represented by the model, but late afternoon simulations showed excessive carbon uptake due to misrepresentation of within‐canopy shading in the model. Interannual variability was not well simulated because only a single year of satellite imagery was used to parameterize the model.

Decaying Scalars Emitted By A Forest Canopy: A Numerical Study - Edward G. Patton; Kenneth J. Davis; Mary C. Barth; Peter P. Sullivan (Boundary-Layer Meteorology, 2001)

Holocene Climate in the Western Great Lakes National Parks and Lakeshores: Implications for Future Climate Change - Margaret Davis; Christine Douglas; Randy Calcote; Kenneth L. Cole; Marjorie Green Winkler; Robyn Flakne (Conservation Biology, 2000)
We reconstruct Holocene climate history ( last 10,000 years) for each of the U.S. National Park Service units in the western Great Lakes region in order to evaluate their sensitivity to global warming. Annual precipitation, annual temperature, and July and January temperatures were reconstructed by comparing fossil pollen in lake sediment with pollen in surface samples, assuming that ancient climates were similar to modern climate near analogous surface samples. In the early Holocene, most of the parks experienced colder winters, warmer summers, and lower precipitation than today. An exception is Voyageurs National Park in northern Minnesota where, by 8000 years ago, January temperatures were higher than today. The combination of high mean annual temperature and lower precipitation at Voyageurs resulted in a dry period between 8000 and 5000 years ago, similar to the Prairie Period in regions to the south and west. A mid‐Holocene warm‐dry period also occurred at other northern and central parks but was much less strongly developed. In southern parks there was no clear evidence of a mid‐Holocene warm‐dry period. These differences suggest that global model predictions of a warm, dry climate in the northern Great Plains under doubled atmospheric CO 2 may be more applicable to Voyageurs than to the other parks. The contrast in reconstructed temperatures at Voyageurs and Isle Royale indicates that the ameliorating effect of the Great Lakes on temperatures has been in effect throughout the Holocene and presumably will continue in the future, thus reducing the potential for species loss caused by future temperature extremes. Increased numbers of mesic trees at all of the parks in the late Holocene reflect increasing annual precipitation. This trend toward more mesic conditions began 6000 years ago in the south and 4000 years ago in the north and increased sharply in recent millennia at parks located today in lake‐effect snow belts. This suggests that lake‐effect snowfall is sensitive to continental‐scale changes in climate and could be affected by future climate change. Plant and animal species sensitive to changes in the moisture regime could thus be endangered within the Great Lakes parks.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Modeling inhibition of type II units in the dorsal cochlear nucleus - Kenneth E. Hancock; Kevin A. Davis; Herbert F. Voigt (Biological Cybernetics, 1997)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)